Structural sensitivity of mesoporous alumina for copper catalyst loading used for NO reduction in presence of CO - Patel, A.; Shukla, P.; Chen, J.; Rufford, T.; Wang, Shaobin; Rudolph, V.; Zhu, Z. (Institution of Chemical Engineers, 2015)
Copper oxide supported on mesoporous alumina pre-treated at different temperatures was examined for catalytic reduction (SCR) of NO with CO. About 4.5% copper oxide was loaded on mesoporous alumina using wet impregnation method. Detailed investigations concluded that the activity of Cu/m-Al2O3 is strongly influenced by the active Cu phase present on bulk copper aluminate. The Copper phase on the catalyst was strongly affected by pre-treatment temperature of the host material. The optimal pre-treatment temperature of the support was found to be around 900 °C. The reaction mechanism on the catalyst surface was suitably described using L-H mechanistic model with the reduced Cuδ+ sites generated on the catalyst surface post CO oxidation playing a critical role in NO reduction.